2012
DOI: 10.5942/jawwa.2012.104.0004
|View full text |Cite
|
Sign up to set email alerts
|

Controlling trace organic contaminants with GAC adsorption

Abstract: FIGURE 9Example plot of single-adsorber use rate versus DOC 0 for control of MIB, DOC, and SMX DOC C/C0 = 0.3 Use rates for DOC were developed from the Zachman and Summers2010) model. DOC-dissolved organic carbon, EBCT-empty bed contact time, GAC-granular activated carbon, MIB-2-methylisoborneol, SMX-sulfamethoxazole Bituminous GAC, EBCT = 10 min MIB C/C0 = 0.1 MIB C/C 0 = 0.2 MIB C/C0 = 0.5 SMX C/C0 = 0.5 SMX C/C0 = 0.2 SMX C/C0 = 0.1 DOC C/C0 = 0.5 DOC C/C 0 = 0.7Corwin & Summers | http://dx.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
30
1
1

Year Published

2014
2014
2023
2023

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 54 publications
(37 citation statements)
references
References 15 publications
(26 reference statements)
4
30
1
1
Order By: Relevance
“…At both EBCTs, 1,2 DCA breakthrough occurs about 30% earlier in the CO II GW, the water with the highest influent TOC. The reduction in target compound performance at higher influent TOC concentrations has been reported and modeled for 1,2 DCA (Kempisty & Summers, 2016) and other target compounds (Corwin & Summers, 2012;Kennedy, Reinert, Knappe, Ferrer, & Summers, 2015;Summers, Kim, Shimabuku, Chae, & Corwin, 2013). In contrast, comparing the CO I and OH GWs did not result in significant differences.…”
Section: Effects Of Varying Background Matrixmentioning
confidence: 90%
“…At both EBCTs, 1,2 DCA breakthrough occurs about 30% earlier in the CO II GW, the water with the highest influent TOC. The reduction in target compound performance at higher influent TOC concentrations has been reported and modeled for 1,2 DCA (Kempisty & Summers, 2016) and other target compounds (Corwin & Summers, 2012;Kennedy, Reinert, Knappe, Ferrer, & Summers, 2015;Summers, Kim, Shimabuku, Chae, & Corwin, 2013). In contrast, comparing the CO I and OH GWs did not result in significant differences.…”
Section: Effects Of Varying Background Matrixmentioning
confidence: 90%
“…Ruhl et al (2014b) carbon usage rate) (Ternes et al, 2002). Corwin and Summers (2012) reported that the breakthrough of sulfamethoxazole occurred significantly earlier compared to diclofenac and Snyder et al (2007) observed a 20% breakthrough of sulfamethoxazole after 9370 bed volumes compared to 34,000 bed volumes until the carbamazepine breakthrough. Adsorption processes for OMP removal are generally more efficient in water with low concentrations of competing organic constituents (low DOC) compared to waters with high DOC loadings such as WWTP effluents (Yu et al, 2008).…”
Section: Adsorptive Omp Removal By Activated Carbonmentioning
confidence: 97%
“…The initial concentrations therefore have a complex influence on the GAC adsorption performance in this study, and breakthrough curves do not superimpose each other when expressed on a concentration normalized basis in contrast to what was previously found for GAC adsorption of other micropollutants. 41,42 This could be explained by the impact of organic matter and biofilms which can enhance the sorption capacity for PFASs in the GAC column treating reject water in comparison to the GAC column treating raw water. When considering the total loading, the Lin-Huang model predicts that in the present study GAC was more efficient at removing PFASs from membrane concentrate than from raw water.…”
Section: Column Half-time Of Saturation and Total Loadingmentioning
confidence: 99%